2021
DOI: 10.1016/j.redox.2021.101939
|View full text |Cite
|
Sign up to set email alerts
|

Redox profile of breast tumor and associated adipose tissue in premenopausal women - Interplay between obesity and malignancy

Abstract: One of the underlying mechanisms that could link breast cancer and obesity is shifted redox homeostasis in the tumor microenvironment. To reveal the relationship between the malignant phenotype and obesity, we compared redox profiles of breast tumor and tumor-associated adipose tissue from premenopausal women: normal-weight with benign tumors, overweight/obese with benign tumors, normal-weight with malignant tumors, and overweight/obese with malignant tumors. Namely, we examined the protein expression of nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the risk of BC recurrence rises in the presence of obesity [ 5 ] with negative effects on treatment efficiency [ 6 ]. One underlying mechanism that could explain the link between obesity and BC is the disrupted redox homeostasis, which is commonly present in breast and adipose tissues of BC women [ 7 ]. Weight gain after diagnosis is also usual in BC and has been associated with greater all-cause mortality rates when compared to BC women of unaltered body weight [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the risk of BC recurrence rises in the presence of obesity [ 5 ] with negative effects on treatment efficiency [ 6 ]. One underlying mechanism that could explain the link between obesity and BC is the disrupted redox homeostasis, which is commonly present in breast and adipose tissues of BC women [ 7 ]. Weight gain after diagnosis is also usual in BC and has been associated with greater all-cause mortality rates when compared to BC women of unaltered body weight [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, adipose tissue dysfunction is one of the hallmarks of obesity and related metabolic disorders. Obesityinitiated oxidative stress leads to increased lipid peroxidation in adipose tissue and the formation of reactive aldehyde byproducts malondialdehyde (MDA), 4-hydroxynonenal (4-HNE), and acrolein [84,85]. It has been shown that MDA can cause frameshift mutations and substitutions in sequences rich in repetitive CG [86].…”
Section: Obesity-induced Oxidative Stress Causes Dna Instabilitymentioning
confidence: 99%
“…Oxidative stress, obesity-related as well as in general, has an important role in cell transformation and cancer development, with similar mechanisms determining the process (Figure 4). The transformed cells protect themselves by upregulating antioxidant enzymes and introducing metabolic adjustments to avoid cell death [17,85,93]. In fact, metabolic reprogramming is one of the prerogatives in the earlystage transition from normal to transformed cells since new demands are emerging, such as rapid proliferation [93].…”
Section: So It Begins: Obesity-related Cell Transformation and Tumor ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed that adipose tissue-expressing lactate dehydrogenase B was found in close proximity to cancer tissue rich in lactate and expressing lactate dehydrogenase A [ 25 ]. Moreover, we showed that such complementary metabolic reprogramming was underpinned by redox reprogramming favoring increased antioxidant defense levels in both breast cancer and cancer-associated adipose tissue [ 26 ].…”
Section: Introductionmentioning
confidence: 99%